2013
DOI: 10.1371/journal.pone.0068120
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-C Irradiation: A Novel Pasteurization Method for Donor Human Milk

Abstract: BackgroundHolder pasteurization (milk held at 62.5°C for 30 minutes) is the standard treatment method for donor human milk. Although this method of pasteurization is able to inactivate most bacteria, it also inactivates important bioactive components. Therefore, the objective of this study was to investigate ultraviolet irradiation as an alternative treatment method for donor human milk.MethodsHuman milk samples were inoculated with five species of bacteria and then UV-C irradiated. Untreated and treated sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 32 publications
3
66
0
5
Order By: Relevance
“…The finding that UV-C irradiation caused less damage to proteins than thermal pasteurization agrees with a previous study conducted with whey protein solutions [37]. We have recently shown that a dosage of 4863 J/l reduces vegetative bacteria by 5-log 10 in human milk with a high total solids content without the loss of BSSL, ALP and fatty acids [29]. However, we also found a positive linear relationship between the dosage required for bacterial reduction and the total solid content in human milk [29].…”
Section: Discussionsupporting
confidence: 88%
“…The finding that UV-C irradiation caused less damage to proteins than thermal pasteurization agrees with a previous study conducted with whey protein solutions [37]. We have recently shown that a dosage of 4863 J/l reduces vegetative bacteria by 5-log 10 in human milk with a high total solids content without the loss of BSSL, ALP and fatty acids [29]. However, we also found a positive linear relationship between the dosage required for bacterial reduction and the total solid content in human milk [29].…”
Section: Discussionsupporting
confidence: 88%
“…Human milk also contains AP activity, though in much lower activity concentration than in bovine milk [72], and its role and benefit to offspring is now questioned [73].…”
Section: Milk and Dairy Products Contain An Alkaline Phosphatase Isoformmentioning
confidence: 99%
“…Estudios de la Corporación Cimientos (financiado por el Ministerio de Comercio e Industria en el año 2014) develaron pérdidasEste trabajo fue recibido el 7 de Octubre de 2015 y aceptado para ser publicado el 2 de Junio de 2016. lácteas y productores de la región en infraestructura física, tanques de enfriamiento, equipos de enfriamientos rápidos de leche cruda, capacitación en Buenas Prácticas de Ordeño, si bien ha mejorado la calidad higiénica pues hace una década el RTB / ml era superior a 2 millones, aun se hace necesario continuar con el esfuerzo para reducir la contaminación bacteriana en el origen de la cadena láctea [3]. Trabajos científicos recientes realizados en leches maternas (Fundació Banc de Sang i Teixits de les Illes Balears, 2014) [4], han encontrados buenos resultados en la preservación de leche humana en los bancos maternos empleando rayos ultravioletas (UV), utilizando lámparas de 40 watt de 78 cm, con tiempos de 10 minutos (48.000 J/l), logrando disminuir bacterias en 5-Log10 [5]; incluso ya existe la patente No. WO 2014094189 A1 [6].…”
Section: Introductionunclassified
“…WO 2014094189 A1 [6]. Pese a los resultados alentadores los investigadores recomiendan la realización de más pruebas para generar masa crítica en el soporte científico que conlleve DOI 10.4067/S0717-75182016000300007 a la implementación masiva de esta técnica emergente [7]; precisamente es lo que el grupo denominado Corporación para la Investigación Tecnológica y Científica-CITEC-consideró prudente desarrollar abordando inicialmente la problemática en su contexto físico y matemático, el planteamiento inicial es referido a los glóbulos grasos lácteos (GGL, por sus iniciales en español) por ser los principales agentes ópticos activos en la penetración de los rayos UV en la leche, esto en razón de su estructura, concentración y dimensión física en el alimento referente [8,9]. La Food Drug Administration (FDA por sus siglas en inglés) permite desde noviembre del año 2000 el uso comercial de la luz UV (21 CFR 179.39 para radiación UV y 21 CFR 179.41 para pulsos de luz) para frutas y vegetales, así como para jugos procesados y posteriormente almacenados en refrigeración, el requerimiento de energía para el tratamiento de UV de jugos de frutas, cerca de 2 kW h/m3, es muy inferior que la energía empleada en los tratamientos térmicos, 82 kW h/m3 [10].Matak (2004 -citado por Choudhary y Bandla 2012) estudió la eficiencia de la luz UV en la inactivación de la E.coli K 12 en leches con diferentes porcentaje de grasa en temperaturas de 4°C y 20 °C empleando el aparato CiderSure 3500, encontrando una reducción entre 0.73 y 2,29 log de esta bacteria en leche con los distintos porcentajes de grasa [11].…”
Section: Introductionunclassified